2023
DOI: 10.3389/fonc.2023.1158124
|View full text |Cite|
|
Sign up to set email alerts
|

B-cell lymphoblastic lymphoma following intravenous BNT162b2 mRNA booster in a BALB/c mouse: A case report

Abstract: Unprecedented immunization campaigns have been rolled out worldwide in an attempt to contain the ongoing COVID-19 pandemic. Multiple vaccines were brought to the market, among two utilizing novel messenger ribonucleic acid technology. Despite their undisputed success in decreasing COVID-19-associated hospitalizations and mortality, various adverse events have been reported. The emergence of malignant lymphoma is one of such rare adverse events that has raised concern, although an understanding of the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…An experimental COVID-19 genetic vaccine animal study involving 28 BALB/c mice, aimed at investigating the pathogenesis of myocarditis following modRNA COVID-19 vaccination, unexpectedly provided crucial insights into the carcinogenicity of these products [33]. Fourteen animals received saline solution, while the remaining were intravenously infused with the modRNA vaccine (BNT162b2).…”
Section: Discussionmentioning
confidence: 99%
“…An experimental COVID-19 genetic vaccine animal study involving 28 BALB/c mice, aimed at investigating the pathogenesis of myocarditis following modRNA COVID-19 vaccination, unexpectedly provided crucial insights into the carcinogenicity of these products [33]. Fourteen animals received saline solution, while the remaining were intravenously infused with the modRNA vaccine (BNT162b2).…”
Section: Discussionmentioning
confidence: 99%
“…Anergic side effects, i.e., immune suppression, are presented as virus reactivation where viruses like varicella-zoster virus (VZV) ( 110 , 111 ) and hepatitis C virus ( 112 ) reoccur following COVID-19 mRNA vaccine injection. Furthermore, have also been reported to likely increase the risks in sensitivity to infections ( 100 , 101 , 113 ) and potentially disturbance of cancer immunosurveillance ( 114 117 ). How can a platform both activate and suppress immune responses?…”
Section: Mrna-lnp-associated Adverse Events – Both Inflammatory and I...mentioning
confidence: 99%
“…The observation that protection against omicron infection waned gradually by month after the booster and seventh month and thereafter, the incidence of infection was higher among people who had the booster compared to those with only the primary series ( 119 ), and COVID-19 incidence increases with the number of shots ( 100 102 ) and immunoreactivity decreases ( 97 ), and viruses can reactivate ( 110 , 112 ), and cancer patients relapse or new cancer develop ( 114 117 , 120 ), seems to indicate that exposure to the mRNA-LNP platform puts people or certain people into a semi-immunodeficient/immunosuppressed state. In line with this, mouse studies have shown that even one-time exposure to mRNA-LNP or LNP can inhibit adaptive immune responses and alter innate immune fitness in an inheritable fashion ( 99 ).…”
Section: Tolerogenic Responsesmentioning
confidence: 99%
“…The authors then refer to the uptake of COVID-19 vaccines and even mention the serious side effects of blood clots, which might even increase vaccine hesitancy if patients were not given information weighing these risks against the risk of contracting the virus. If SDM delivers evidence-based, trustworthy information, then people should be informed that COVID-19 is mainly a disease that predominantly affects older people and/or is a serious disease for those with major complications and that the vaccines may have serious adverse effects [23][24][25][160][161][162][163]. Therefore, the aim of SDM should not be to promote a mass vaccination campaign in COVID-19 as this would be unethical in the light of the massive risk differences in different age and morbidity groups [158,164].…”
Section: Sdm Shared Decision Makingmentioning
confidence: 99%